Homegarden Ethnobotany of Two Saibatin Villages in Lampung, Indonesia: Species Diversity, Uses, and Values - Wakhidah, Anisatu Z; Chikmawati, Tatik; Purwanto, Yohanes (Forestry Faculty, Universitas Hasanuddin, 2020)
Since homegardens reflect a culture of a particular ethnic group, the study in homegardens provide unique insights into ethnobotany. The Saibatin sub-tribe in Lampung has extensive uses for plants, but an ethnobotanical study of their homegardens are still lacking. This study aimed to describe the structure and composition of the Saibatin community homegarden and to explain the diversity of plants and the usage patterns through an ethnobotany perspective. The study also aimed to elaborate species with social-economic and ecological functions and to describe the overall functions of homegardens. Ethnobotanical data were collected using participant observation methods, which were complemented by questionnaires. We determined the key respondents and common respondents using the purposive sampling and snowball sampling method, while homegarden plant species diversity was identified using vegetation analysis methods. The results showed that 3 size categories of homegardens are present in this area, including narrow, medium, and broad. The homegarden structure consisted of hadap/tangebah (front yard), gelekhan (side yard), and kudan (backyard). Six types of habitus composed the homegarden structure, namely herbaceous, epiphytes, shrubs, trees, succulents, and vines. The homegarden species richness index (DMg) in Way Jambu Village (WJA) (17.34) was higher than Labuhan Mandi Village (LMA) (16.87). Even so, the homegarden plant diversity (H’) and evenness (J ) in LMA was higher than WJA. There were 16 plant usage categories used by the Saibatin community (WJA 15; LMA14). Foodstuffs were the usage category of homegardens with the highest number of species in both villages. The species ICS value ranges between the two villages were relatively similar. The highest ICS species in WJA was Cocos nucifera while in LMA was Cymbopogon citratus. By studying ethnobotany of Saibatin sub-tribe homegarden we conclude that the three main roles of the homegardens are to provide social-economic impacts, ecological services, and representing the cultural value of Saibatin community identity